Phytophthora kernoviae and P. ramorum: host susceptibility and sporulation potential on foliage of susceptible trees1 - Denman, S.; Kirk, S.; Whybrow, A.; Orton, E.; Webber, J. F. (EPPO Bulletin, 2006)
Phytophthora kernoviae and P. ramorum are introduced, invasive pathogens in the UK. Both species are adapted for aerial dispersion and have a wide host range, many of which are common to both pathogens. The diseases they cause are foliar necrosis and shoot tip dieback on both tree and ornamental hosts, and bleeding cankers on tree hosts. Inoculum is produced on infected foliage but not on bleeding cankers in both cases. Proactive measures to prevent disease spread and to evaluate the risks posed by these pathogens are being undertaken. Amongst others, these include using the detached leaf assay to get an indication of tree foliage susceptibility, and inoculating wounded stems of saplings to get an idea of under-canopy sapling and nursery tree susceptibility. The sporulation potential on selected susceptible hosts was assessed, and finally, surveys which are still ongoing were carried out in south-west England. Results of this work are presented and discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: host tree; Phytophthora kernoviae; Phytophthora ramorum; resistance; sporulation potential (voyant); susceptibility